Three-Dimensional Devices Transport Simulation Lifetime and Relaxation Semiconductor - Nouar Fadila Souad; Mansouri Seddik; Amrani Mohamed; Marie Pierre; Massoum Ahmed (Institute of Advanced Engineering and Science, 2015)
Our work is to create a three-dimensional Simulator (3D) used for the study of the components to low geometry of design, and to determine in the volume structure the potential distributions and densities of free carriers in bias voltage given by solving the system of Poisson and two continuities equations. The initial version can simulate components of lifetime semiconductor. In this study, we make a comparison between the lifetime and relaxation semiconductor in the conduction mode. In order to create a larger Simulator, we'll perform a calculation by varying am bipolar lifetime way to move from lifetime semiconductor to relaxation semiconductor. We consider the case corresponding at two different values of diffusion lifetime τ0 which is corresponding to a measured lifetime in current transport. The method of resolution consists to linearization of the equations transport by the finite differences method. The algorithm for solving linear and strongly coupled equations deduced from the physical model is the Newton-Raphson. However, in order to allow a better convergence and consequently an improvement of time computing 3D, a method combined, incorporating the Newton algorithm and the Gummel method was developed. PIN diodes are used for test of the simulation model